2011
DOI: 10.1073/pnas.1014993108
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle restriction by histone H2AX limits proliferation of adult neural stem cells

Abstract: Adult neural stem cell proliferation is dynamic and has the potential for massive self-renewal yet undergoes limited cell division in vivo. Here, we report an epigenetic mechanism regulating proliferation and self-renewal. The recruitment of the PI3K-related kinase signaling pathway and histone H2AX phosphorylation following GABA A receptor activation limits subventricular zone proliferation. As a result, NSC self-renewal and niche size is dynamic and can be directly modulated in both directions pharmacologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
118
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 44 publications
3
118
0
3
Order By: Relevance
“…We propose that physiological levels of GABA synthesized by SSCs or interstitial cells through GABA A receptors result in a decreased proliferation of SSCs. GABA control over proliferation is also found in ES cells and adult neural stem cells, even in tumors where putative cancer stem cells reside, suggesting a developmentally conserved role of GABA as a negative regulator of stem cell proliferation [19,20,38]. In conclusion, our study provides direct evidence that the GABA system is present in mouse SSCs, and indicates that GABA inhibits SSC proliferation independently of apoptosis in vitro.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…We propose that physiological levels of GABA synthesized by SSCs or interstitial cells through GABA A receptors result in a decreased proliferation of SSCs. GABA control over proliferation is also found in ES cells and adult neural stem cells, even in tumors where putative cancer stem cells reside, suggesting a developmentally conserved role of GABA as a negative regulator of stem cell proliferation [19,20,38]. In conclusion, our study provides direct evidence that the GABA system is present in mouse SSCs, and indicates that GABA inhibits SSC proliferation independently of apoptosis in vitro.…”
Section: Discussionmentioning
confidence: 52%
“…The inhibitory effect of GABA on cell proliferation is not restricted to the nervous system. GABA has recently been shown to limit the proliferation of pluripotent embryonic stem cells and adult neural stem cells [19,20]. In light of these recent findings, we investigated whether GABA is present in SSCs and if it influences their proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, this niche provides the appropriate environment for stem and progenitor cells, including RGLs, and niche signals are crucial in adult neurogenesis (Ming and Song, 2011). Work from several laboratories during the past decade has revealed that neurotransmitters provide important components of the niche signals and influence several aspects of neurogenesis, both during normal physiological conditions and in disease models (discussed further below) (Höglinger et al, 2004;Liu et al, 2005;Berg et al, 2011;Fernando et al, 2011;Alfonso et al, 2012). …”
mentioning
confidence: 99%
“…H2AX is required for cell cycle arrest and DNA repair following doublestranded DNA breaks [38,39] . DNA damage results in the rapid phosphorylation of H2AX by ATM [38,40] . Within minutes of DNA damage, H2AX is phosphorylated at the sites of the DNA damage [38] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ATM/H2AX signaling pathway is important in the response to and repair of DNA damage induced by OS [38,41] . Our results with ATM and H2AX clearly showed that OS after liver surgery caused DNA damage signaling and triggered subsequent DNA repair.…”
mentioning
confidence: 99%